Long-Term Study on Medium-Scale Traveling Ionospheric Disturbances Observed over the South American Equatorial Region - Patrick Essien (MDPI AG, 2021)
Using data collected by the GNSS dual-frequency receivers network, de-trended TEC maps were generated to identify and characterize the medium-scale traveling ionospheric disturbances (MSTIDs) over the South American equatorial region (latitude: <semantics>0∘</semantics> to <semantics>15∘</semantics> S and longitude: <semantics>30∘</semantics> to <semantics>55∘</semantics> W) during solar cycle 24 (from January 2014 to December 2019). A total of 712 MSTIDs were observed during quiet geomagnetic conditions. The Frequency of occurrence of MSTID is high during the solar maximum and low in the minimum phase. This might be due to the solar cycle dependence of gravity wave activity in the lower atmosphere and gravity wave propagation conditions in the thermosphere. The predominant daytime MSTIDs, representing 80% of the total observations, occurred in winter (June-August season in the southern hemisphere) with the secondary peak in the equinox; while the evening time MSTIDs, representing 18% of the entire events, occurred in summer (December to February season) and equinox (March to May and September to November), and the remaining 2% of the MSTIDs were observed during nighttime. The seasonal variation of the MSTID events was attributed to the source mechanisms generating them, the wind filtering and dissipation effects, and the local time dependency. The horizontal wavelengths of the MSTIDs were mostly concentrated between 500 and 800 km, with the mean value of 667 ± 131 km. The observed periods ranged from 30 to 45 min with the mean value of 36 ± 7 min. The observed horizontal phase speeds were distributed around 200 to 400 m/s, with the corresponding mean of 301 ± 75 m/s. The MSTIDs in the winter solstice and equinoctial months preferentially propagated northeastward and northwestward. Meanwhile, during the summer solstice, they propagated in all directions. The anisotropy of the propagation direction might be due to several reasons: the wind and dissipative filtering effects, ion drag effects, the primary source region, and the presence of the secondary or tertiary gravity waves in the thermosphere. Atmospheric gravity waves from strong convective sources might be the primary precursor for the observed equatorial MSTIDs. In all seasons, we noted that the MSTIDs propagating southeastward were probably excited by the likely gravity waves generated by the intertropical convergence zone (ITCZ).